REKONSTRUKSI DAN INVESTIGASI DIGITAL FORENSIK PADA APLIKASI WHATSAPP DENGAN METODE NIST : KASUS PELECEHAN SEKSUAL - Ginting, Jusia Amanda; Setiawan, Harry; Andry, Johannes Fernandes; Ngurah Suryantara, I Gusti (ISTEK WIDURI, 2024)
The rapid advancement of technology, especially during the pandemic, has drastically changed the way we conduct activities, with the majority now being carried out online through smart devices such as smartphones. However, along with this progress comes new challenges in the form of cybercrime, increasingly known as cybercrime. Cybercrime on mobile platforms, known as mobile cybercrime, encompasses various activities such as fraud, spreading hoaxes, pornography, and sexual harassment. This research aims to examine the effectiveness of cybercrime investigation methods, particularly in cases of sexual harassment, with a focus on the WhatsApp platform. The method used is the National Institute of Standards Technology (NIST), implemented using appropriate tools to support this research. The testing process involves four main stages: data collection, examination, analysis, and reporting. This includes steps such as securing the device, acquiring data, and analyzing it using software such as FTK Imager and WhatsApp Viewer. The test results show that most deleted messages can be recovered, although messages deleted using the